Staffing in cardiology in the United Kingdom 1990. Sixth biennial survey: with data on facilities in cardiology in England and Wales 1989. Issue 5 (November 1991) - Chamberlain, D; Pentecost, B; Reval, K; Stevens, J; Boyle, D M; Cobbe, S; Ballantyne, D; Shaw, T
Abstract : The Sixth Biennial Survey of Staffing in Cardiology was conducted in July 1990. This report summarises the data that were collected, together with the results of a survey of facilities in cardiology made in 1989. The total number of cardiologists in the United Kingdom, defined as individuals trained in the specialty and spending at least 40% of their time working in it, is now 323. Six individuals work part time only, making 320 whole time posts. This number has increased over the two years from 1988 to 1990 by 32, of which 23 work only in the specialty and nine as general physicians with a major interest in cardiology. The rate of increase in numbers over the past decade has been reasonably consistent with an average of approximately 4.4% per year. Thirty one districts in England and Wales still have no cardiologist and 13 other districts have little provision with an average of three (visiting) sessions each per week. The population in these 44 districts is 8.3 million. Scotland also has an inadequate distribution of service in the specialty. If recommendations for cardiac surgery and angioplasty made in the Fourth Report of a Joint Cardiology Committee of the Royal College of Physicians of London and the Royal College of Surgeons of England are to be met, we calculate that we need 63 more cardiologists in our major centres. To provide one cardiologist in every district hospital and two for larger districts would require 94 more specialists, making a total shortfall of 157 individuals. We have no excess of senior registrars to provide for a major expansion at consultant level. Time spent within the senior registrar (or academic equivalent) grade has tended steadily to decline and very few now reach the end of their contracts. The need for more individuals to pass through the senior registrar grade will be met in part by a planned reduction in the training period to three years. This will be inadequate, however, because projected retirements show that the number of consultant vacancies will increase sharply from 1997. We believe that additional senior registrar posts must be created if a serious shortfall in service provision by consultants is to be avoided. The provision of non-invasive facilities in cardiology is reasonable. The need for additional equipment for invasive cardiology has not been assessed. The number of physiological measurement technicians varies considerably between regions and is generally inadequate.